IMPLEMENTATION ANALYSIS OF IJARAH AL-MUNTAHIAH BI AL-TAMLIK (IMBT) IN SHARIA LEASING - Sundari Sundari; Efi Nurhidayah; Ubaid Aisyul Hana (Dirosatuna: Journal of Islamic Studies, 2022)
Leasing is one type of financial institution. Financial institutions can be regarded as alternative sources of financing whose activities are carried out by providing funds or capital goods by not withdrawing funds directly from the public in the form of demand deposits, deposits, savings, and promissory notes. This research is library research, which studies collecting library data. The nature of this research is a descriptive analysis that explains the legal relationship in sharia leasing contained in the contracts that frame it, namely the Ijarah contract and the ijarah al-muntahiyah bi al-tamlik contract. In pledging a sharia leasing object, the customer is not authorized to guarantee the object because the object is still the property of the lessor. At the same time, the lessee has yet to become the owner of the object. This applies to both Ijarah contracts and ijarah al-muntahiyah bi al-tamlik contracts. In the ijarah al-muntahiyah bi al-tamlik contract, there is only a transfer of ownership at the end of the lease period. During the rental period, the customer is only a tenant, not yet an owner. So that leasing is no longer taboo for the people of Indonesia. Moreover, in Islam, there is no prohibition on sharia leasing. Its development is also increasing, considering the increasing needs of the community. Sharia leasing cannot be separated from ijarah al-muntahiyah bi al-tamlik, usually abbreviated as IMBT.